2021
DOI: 10.1002/ece3.7232
|View full text |Cite
|
Sign up to set email alerts
|

Female extra‐pair behavior is not associated with reduced paternal care in Thorn‐tailed Rayadito

Abstract: Extra-pair behavior is present in ~76% of all socially monogamous birds with biparental care whose genetic mating system has been described through molecular methods (Brouwer & Griffith, 2019). This behavior consists of males and females copulating with individuals other than their social partner, and as a consequence, broods of socially monogamous pairs may have several genetic fathers (Kempenaers & Schlicht, 2010).From extra-pair behavior, males can obtain a direct benefit on fitness by increasing the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…The average clutch size is five eggs (range: 1–10) in this population (Poblete et al . 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average clutch size is five eggs (range: 1–10) in this population (Poblete et al . 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Timing of breeding was defined for each breeding pair as the difference between the first‐egg date and the date when the first egg in the population was laid (see Verhulst & Tinbergen 1991, Abbey‐Lee & Dingemanse 2019, Poblete et al . 2021). Breeding adults were captured inside the nestboxes using a triggered trap when nestlings were 12–14 days old (Quirici et al .…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have been performed linking paternity and paternal care, showing support for both a reduction in care [31,77,[140][141][142], and no effect on care [136,[143][144][145][146]. In the reed bunting Emberiza schoeniclus, Suter et al [141] showed that the males reduced provisioning rate in response to decreased paternity.…”
Section: ) Reduced Parental Carementioning
confidence: 99%